Strengthening Religious Values and Environmental Concerns: A Pro-environmental Behavior Education Program for Adolescent Santri in Indonesia - Rapotan Hasibuan; Radinal Mukhtar Harahap; Syafran Arrazy; Fifi Afifah Hasibuan; Wafida Tunnur Siregar; Diva Keysha Aura Silalahi (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
Climate change and environmental degradation have become urgent global challenges, marked by the significant rise in average global temperatures due to human activity, industrialization, and carbon emissions. The low level of environmental concern in Indonesia worsens this challenge, as reflected by the Environmental Care Behavior Index (ECBI/ IPRLH) of only 0.57 (low category). Furthermore, only 38% of Indonesian adolescents are actively involved in environmental preservation. Initial observations at Pesantren Ar-Raudlatul Hasanah Medan indicate that high institutional compliance does not fully translate into individual pro-environmental actions by santri (students). This is evidenced by inconsistent waste segregation, reliance on single-use plastics, and limited water conservation. This community service activity aimed to enhance religiosity toward environmentally friendly behavior among adolescent santri. The CBPR model was implemented from July to October 2025 at the pesantren. The results indicated that the santri’s level of religiosity was in the high category across all dimensions, and their pro-environmental behavior was categorized as good to very good, especially concerning waste disposal discipline and water conservation. Spiritual values (such as amanah and ihsan) have reached affective and behavioral stages. However, personal initiatives, such as sorting waste or reducing single-use plastic, require further strengthening. It is concluded that pesantren hold significant potential as a foundation for forming religiously rooted pro-environmental behavior.